ANALYSIS OF INTERNATIONAL NON-GOVERNMENTAL ORGANIZATIONS ACTIVITY IN THE CONTEXT OF GLOBALIZATION - Baluta I.V. (Pressing Problems of Public Administration, 2017)
In the article the activities of international NGOs in the context of globalization; the basic features and functions of international NGOs; analyzes the main elements of the legislative activities of international NGOs; is considered information interaction international NGOs and civil society and other actors in international political relations; singled out the role of international non-governmental organizations in international relations in terms of global social transformation.